2016
DOI: 10.13075/mp.5893.00462
|View full text |Cite
|
Sign up to set email alerts
|

Attenuating effects of caffeic acid phenethyl ester with intralipid on hepatotoxicity of chlorpyrifos in the case of rats

Abstract: Background: Chlorpyrifos (CPF), insecticide widely used in agriculture, may cause poisonings in the case of humans. As a result, there is a large amount of treatment research underway to focus on the possibility of chlorpyrifos induced poisonings. The aim of this study has been to evaluate the effects of caffeic acid phenethyl ester (CAPE) and intralipid (IL) on hepatotoxicity induced by chlorpyrifos in the case of rats. Material and Methods: The rats in this study were treated with CPF (10 mg/kg body weight (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…It has been reported that caffeic acid has a number of pharmacological activities—antidiabetic, antihypertensive, antioxidant, immunomodulatory, and anti‐inflammatory properties (Challis & Bartlett, ; Chan & Ho, ; Chiou, Sung, Huang, & Lin, ; Gulcin, ). Dokuyucu et al () reported the attenuating effects of caffeic acid phenethyl ester with intralipid on hepatotoxicity of chlorpyrifos in rats while Habtemariam (in press) reported the protective effects of caffeic acid on the Alzheimer's brain.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that caffeic acid has a number of pharmacological activities—antidiabetic, antihypertensive, antioxidant, immunomodulatory, and anti‐inflammatory properties (Challis & Bartlett, ; Chan & Ho, ; Chiou, Sung, Huang, & Lin, ; Gulcin, ). Dokuyucu et al () reported the attenuating effects of caffeic acid phenethyl ester with intralipid on hepatotoxicity of chlorpyrifos in rats while Habtemariam (in press) reported the protective effects of caffeic acid on the Alzheimer's brain.…”
Section: Introductionmentioning
confidence: 99%